Efek hidrogel getah jarak cina (Jatropha multifida Linn.) berbasis karagenan kappa dan karagenan iota terhadap penyembuhan luka tikus wistar jantan - Fetri Lestari; Gita Cahya Eka Darma; Rikka Kartika (Universitas Ahmad Dahlan, 2016)
Jatropha multifida Linn. latex has been reported in many study for its activities to treats wound. Preparation of hydrogels containing 3% of Jatropha multifida Linn. latex with variety of base polymers kappa carrageenan and iota carrageenan was conducted and met good characteristics. This study aimed to evaluate effect of both hydrogels to promote wound healing in Wistar rats. Tests carried out on five groups of rats with 1.5 cm diameter of wound in the back area, consisting of a control group, two test groups were each treated by 2% kappa carrageenan-based hydrogel (kappa-hydrogel group) and 2% iota carrageenan-based hydrogel (iota-hydrogel group) of the latex, and two groups were each given a different hydrogel base according to type of hydrogel tested. Effect on wound healing was assessed by parameters including wound drying period, scab forming period, and the change in diameter of the wound. Results show kappa-hydrogel group achieve the most rapid wound healing compare to the control group significantly (p<0,05) and the iota-hydrogel group on wound drying period (16.6 ± 2.2 hours) and scab forming period (92.6 ± 2.2 hours). Kappa-hydrogel group also show best changes in diameter of the wound at day 21 which is reduced to 0.02 ± 0.03 cm, compare to the control group and iota-hydrogel group. As a conclusion, the 2% kappa carrageenan-based hydrogel containing 3% of Jatropha multifida Linn. latex produce better effect to promote wound healing than iota carrageenan-based hydrogel in this study.